Sheet metal forming analysis of aluminium alloy AA6061 using Altair INSPIRE form simulation - Izdihar Tharazi,; Nurul Hayati Abdul Halim,; Farrahshaida Mohd Salleh,; Yupiter HP Manurung,; Amirul Syazani Sabtu,; Zulaika Zulkifli,; Muhammad Ilham Khalit, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Altair INSPIRE Form is a computer simulation developed for designing and modelling sheet metal forming processes. Within the modules, the design and formability prediction can be simulated and optimized. Thus, this study focuses on analysing the formability of sheet metal Aluminium alloy AA6061 by simulating numerically a multistage forming of an end-wall process where the material properties and process parameters gained from the literature were used as input. The geometrical model was validated by comparing its formability with the literature that was simulated by Altair HyperForm. Then, to statistically analyse the influence of forming parameters on formability, Analysis of Variance (ANOVA) was applied with the design of experiment approach using the Response Surface Methodology (RSM). The simulation results observed similar strain rate distributions between Inspire Form and HyperForm under a safe forming process. For the formability of Aluminium alloy AA6061, loose metal zones with wrinkles, excessive thinning up to 23.13%, and the maximum equivalent stress at 414.6 MPa were expected to be generated. These findings clearly explained that forming parameters such as blank holder force and punch velocity have to be carefully controlled for this ductile material. The ANOVA shows a significant influence of coefficient friction and punch velocity on thinning percentages. The likelihood of tearing to form at a higher thinning percentage and its appearance was observed in the Forming Limit Diagram which evaluates its formability. The validation of optimized parameters by simulation work is concluded to be successful as no fracture appeared in this simulation with a small percentage error at 2.19% between the simulation and the predicted value.